The impact of the COVID-19 pandemic on Hebron University EFL Learners’ Anxiety - Mohammed Farrah; Renad S. Dweik; Raghad J. Al Nazer (RIRAI Publisher, 2023)
Due to pandemic the COVID-19 pandemic, the learning situation has moved from traditional to online learning to hold back the further spread of the pandemic. This transformation largely impacted the condition of psychology, specifically anxiety issues. This study examines the impact of COVID-19 on Hebron University (EFL) learners' anxiety in Palestine. The researchers examined the various levels of anxiety triggered by the COVID-19 pandemic among university learners. Additionally, the researchers examined some causes that surge anxiety among learners amidst COVID-19, and the recommendations used by students to lessen the undesirable effects of anxiety on learners amidst COVID-19. The researchers employed both quantitative and qualitative methods to gather data. The researchers collected the data for the study from 70 EFL students at Hebron University. This research demonstrated that COVID-19 triggers high anxiety among the EFL students at Hebron University, Palestine. The researchers concluded with some recommendations.